2016
DOI: 10.1111/bjd.14703
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of interleukin-17 in inflammatory skin diseases

Abstract: Interleukin (IL)-17 is an emerging target for inflammatory skin disorders. Given the remarkable success of its therapeutic inhibition in psoriasis, the pathogenic role of this cytokine is being explored in other immune-mediated diseases. Interestingly, IL-17 is linked to particular skin conditions where its activation coincides with disease flares. The leading hypothesis for its contribution to proinflammatory signalling cascades is driving inflammasome activation. However, IL-17 stimulation also releases a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 73 publications
1
67
0
2
Order By: Relevance
“…10 A complex network of cytokines released by the Th cells is involved in various autoimmune and allergic responses. 15 IL-22 is synthesized and released by Th22, and both IL- 22 and Th22 have been confirmed to play important roles in atopic diseases. 12 The imbalance between Th1 and Th2 has long been considered as a possible mechanism in urticaria.…”
Section: Introductionmentioning
confidence: 99%
“…10 A complex network of cytokines released by the Th cells is involved in various autoimmune and allergic responses. 15 IL-22 is synthesized and released by Th22, and both IL- 22 and Th22 have been confirmed to play important roles in atopic diseases. 12 The imbalance between Th1 and Th2 has long been considered as a possible mechanism in urticaria.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a functional role of IL‐23/Th17 in the immunopathogenesis of psoriasis was demonstrated . Th17 cells are inflammatory Th cells characterized by the expression of IL‐17A/F, IL‐21, IL‐22, and potentially TNF‐α and IL‐6, and a high level of retinoic acid‐related orphan receptors (RORα and RORγ) . Although Th17 cells were originally regarded as the major source of IL‐17 in psoriasis, accumulating evidence suggests that other innate immune cell types, including γδ T cells, innate lymphoid cells (ILCs), NKT cells, and neutrophils, can also produce IL‐17 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors calculated the blood BDNF levels instead of brain BDNF levels and found that these BDNF levels are reduced in depression and psoriasis. Abnormal IL-17 expression has also been observed in psoriatic patients with therapeutic inhibition showing success in reducing disease severity [35,36]. Furthermore, as has been discussed above, inflammatory cytokines like TNF-α, IFN-γ, and other type-1 cytokines play a crucial part in the pathophysiology of psoriasis [26].…”
Section: Immunological Changes In Psoriasismentioning
confidence: 99%